Implementation of Competitive Strategy to Maximize The Value - Martin Pangondian Gultom (Universitas Pendidikan Nasional, 2016)
The development of the hotel industry today has seen to be uncontrolled. Everyyear the new hotels, expecially five stars hotels are built. On the other hand, the totalnumber of tourist who come to Bali is not increase as many as the hotels built. Thedecrease of our money currency, Rupiah, encourage many toursts come to Indonesiaespecially Bali. The investors saw this condition and bring into the opportunity to buildmany hotels in Bali. We could see that more supply rather than demand in thiscircumteces. This condition is also impected to the Competition between those hotelsespecially the five stars hotel as the object of this Reserch. On the other hand, the marketevolusion is also bring the firm to visualize the path as it is impacted by neew needs,competitiors, technology, channels and other development.Padma Resort Legian is in the Market for approximatelly 25 years. The competitionis changing year by year and bring this hotel into the high competition. The hotel need tohave a good Competitive Strategy to win the competition as we know that the other 14new five stars International brand hotels are building until 2019 and will contribute about2.040 rooms. Addition information from STR Global, a company located in USA thatprovide a service of Market Information for Global Hotel Industry said that the Growthof the hotels will impact the Occupancy. The data said that the Occupancy decreased 6.3%compare to the last year in the first quarter. A special attention to January 2016 that theOccupancy in Bali decrease 14.7% become55.8%.Padma Resort Legian make their Competitive Strategy by maximizing theValue. The Competitive Strategy of this hotel consist of Differentiation ( ProductDevelopment) and Focus ( Quality of Service and Customer Relationship Management),these went to Value which consist of Functional Benefit and Emotional Benefit. All thisvariables go to achive the Guest Satisfaction. Again, digital technology is used to thissituation especially in the Customer Relationship Management as well as the measurementof their Guest Satisfaction by using Media System and Trip Advisor Website.Researcher bring this study to clearly see how Padma Legian Resort Baliimplement their Competitive Strategy to maximize the Value. How they implement thecompetitive strategy to maximize the value and how they measure the guestsatisfaction and bring this strategy into succeed to get the guest or customer satisfaction.